Child Care over the Business Cycle - Jessica H. Brown; Chris M. Herbst (Institute of Labor Economics (IZA), 2021)
We estimate the impact of macroeconomic conditions on the child care market. We find that the industry is substantially more exposed to the business cycle than other low-wage industries and responds more strongly to negative shocks than positive ones. Indeed, child care employment requires more time to recover than the rest of the economy. Although the reduction in supply may pose difficulties for parents, we find evidence that center quality is countercyclical. When unemployment rates are higher, child care workers have on average higher levels of education and experience, turnover rates are lower, and consumer reviews on Yelp.com are higher.
Keywords: J13; J21; E32; J24; 330; child care; early childhood education; business cycles